2012
DOI: 10.9790/3013-24304346
|View full text |Cite
|
Sign up to set email alerts
|

Socio demographic factors affecting perinatal mortality- A study in a rural setup

Abstract: Background:-Perinatal mortality is a sensitive indicator of the quality of services provided to pregnant women and their newborn. Perinatal mortality audit in a health care facility helps to determine the important cause of perinatal deaths and take measures to reduce it. This study was carried out to find out the socio demographic causes of perinatal deaths. Material and Methods: -A clinical observational study was undertaken at a tertiary care teaching hospital in a rural area over a period of 1 year from Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 12 publications
0
5
1
3
Order By: Relevance
“…In cohesion to other studies in India, the present study found a statistically significant difference between gender, birth order and gestational age of newborn. 10,12 The findings of this study emphasized the need for the identification of high-risk babies and early postpartum interventions. Relevant strategies include special training to birth attendants in resuscitation, immediate postnatal check-up in the home for high-risk babies identified at delivery and promotion of institutional deliveries.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In cohesion to other studies in India, the present study found a statistically significant difference between gender, birth order and gestational age of newborn. 10,12 The findings of this study emphasized the need for the identification of high-risk babies and early postpartum interventions. Relevant strategies include special training to birth attendants in resuscitation, immediate postnatal check-up in the home for high-risk babies identified at delivery and promotion of institutional deliveries.…”
Section: Discussionmentioning
confidence: 80%
“…[6][7][8][9] Corroborated by the results of studies in India, our study found substantial differences in deaths due to residence, where rural area accounted for a larger proportion of deaths than urban area. [10][11][12] The residence difference in neonatal mortality may be due to deprived health facility services and poor referral system.…”
Section: Discussionmentioning
confidence: 99%
“…Durante la gestación, tanto madre como feto se encuentran expuestos a factores de riesgo que de manera directa o indirecta influyen en el desarrollo normal del embarazo, estos amenazan la salud, la vida y en gran parte conllevan a desenlaces fatales; sin embargo, la información que se tiene actualmente no es del todo concluyente acerca de las causas que generan la mortalidad fetal, razón por la cual aún no se ha considerado como un problema prioritario de salud pública, carece de estrategias de intervención y sus repercusiones son serias en la vida familiar (8,13) . Generalmente, se considera que es un evento determinado por un componente clínico y patológico de la madre o del feto.…”
Section: Discussionunclassified
“…Surekha et al desarrollaron a cabo estudios en India durante el mismo periodo de tiempo, encontrando que la mortalidad perinatal fue más frecuente en la zona rural, en una situación socioeconómica baja y ninguna de las mujeres pertenecían a la clase social media alta o superior; la mayoría de ellas no tenían educación y solo un 1% alcanzaron a graduarse, resultados que en estos aspectos difieren del presente estudio, pero que si manifiestan una relación concluyendo que la disminución de peso fetal es inversamente proporcional a la muerte perinatal, es decir, a mayor peso adquirido por el feto durante la gestación, menor será su riesgo de morir intrautero (8) .…”
Section: Discussionunclassified
See 1 more Smart Citation